Revision of Macropygium Spinola, 1837 (Hemiptera: Pentatomidae: Ochlerini) with the revalidation of three species and the description of one new species - Da Silva, Layse Mitsue Harada; Campos, Luiz Alexandre (Zootaxa, 2021)
The Ochlerini (Discocephalinae) are endemic in the Neotropical region, and the tribe currently contains 38 genera and 149 species. The monotypic Macropygium Spinola, 1837 is the most widespread ochlerine genus in the Americas, ranging from Mexico to Argentina. Macropygium reticulare (Fabricius, 1803) is one of the few Ochlerini of phytosanitary importance, transmitting Phytomonas spp. in palm crops in South America. Nonetheless its wide distribution, and phytosanitary importance, the taxonomy of Macropygium has been neglected. Here we present a revision of Macropygium, revalidate three species, Macropygium spinolae Stål, 1860, REVISED STATUS (removed from the synonymy with M. reticulare), Macropygium bifidum (Westwood, 1837), NEW COMBINATION (removed from the synonymy with M. reticulare), and Macropygium subsulcatum (Amyot & Serville, 1843), REVISED STATUS (removed from the synonymy with M. reticulare). We remove Ochlerus guttipes Walker, 1867 from the synonymy with M. reticulare, and propose O. guttipes a new junior synonym of M. spinolae. Finally, we describe one new species, Macropygium graziae Silva & Campos, Sp. Nov.. A key for the species of Macropygium is provided.